Food Offerings at the Baritan Ceremony in Asemdoyong, Pemalang Regency: An Ethnolinguistic Study - Sarwiji Suwandi; Titi Setiyoningsih; Chafit Ulya; Ari Suryawati Secio Chaesar; Eko Setyawan; Sugit Zulianto (Universitas Muhammadiyah Malang, 2025)
The Baritan ceremony in Asemdoyong, Pemalang Regency, is a traditional ritual still maintained and preserved by the local community. In this ceremony, various food offerings are prepared as a form of honour and offering to the ancestors and the Creator. This study aims to analyse the ethnolinguistic meaning of food offerings in the Baritan ceremony and to understand how this tradition plays a role in maintaining the cultural identity of the Asemdoyong community. Data were obtained from observations and interviews with people who carry out the Baritan tradition. The results showed that the meaning contained in food offerings consisting of tumpeng, side dishes, vegetables, pala pendem, pala gantung, fruit, compote, and market snacks wrapped in leaves in the Baritan tradition ceremony in Asemdoyong, Pemalang Regency represents the hope for sustenance obtained from the surrounding nature, expressions of gratitude and requests for prosperity to God, and harmony of social relations through speech and action. Food offerings play a role in representing harmonious relationships between humans and others, God, and the natural environment. Islamic values dominate the meaning due to the influence of Islamic teachings adopted by the community. Thus, preserving this tradition is crucial to maintaining cultural identity and enriching Indonesia's cultural heritage.